Effect of Somatic Experiencing Resiliency-Based Trauma Treatment Training on Quality of Life and Psychological Health as Potential Markers of Resilience in Treating Professionals - Winblad, Neal E.; Changaris, Michael; Stein, Phyllis K. (Frontiers in Neuroscience, 2018)
Abstract Background: Individuals who treat trauma are at significant risk of vicarious traumatization and burnout. Somatic Experiencing® (SE) is a resiliency-focused trauma treatment modality designed to address health and mental health symptoms impacted by autonomic nervous system (ANS) dysregulation, e.g., anxiety, depression, post-traumatic stress disorder, migraines, fibromyalgia, and chronic fatigue. SE® training supports the development of clinical skills to reduce health/mental health symptoms as well as increase clinician resilience. Individuals who display resilience often have increased experiences of wellbeing (quality of life) and decreased levels of self-reported psychological symptoms. Greater resilience could mitigate the risks to providers and the clients they treat. Materials and Methods: This within-groups, longitudinal study assessed students (N=18) over the course of a 3-year SE practitioner training. This training focuses on increased ANS, physical, and emotional regulation skills. A web-based survey including: measures of a general quality of life (WHOQOL-BREF), psychological symptoms, somatic, anxiety, and depressive symptoms (PHQ-SADS), as well as a measure of early life exposure to adversity (CDC/Kaiser Permanente ACE Score Calculator Questionnaire) was conducted yearly. Results: ANOVA with repeated measures showed that there were significant reductions in anxiety symptoms (GAD7, p < 0.001) and somatization symptoms (PHQ15, p<0.001). Health-related quality of life (a measure of physical wellbeing) and social quality of life (a measure of interpersonal wellbeing) both increased significantly (Health QoL p =0.028; Social QoL p =0.046). Conclusions: Results suggest that professionals attending the 3-year SE® training experience a significant improvement in self-reported measures associated with resiliency including: quality of life (wellbeing) and psychological symptoms (anxiety and somatization). Our results support the importance of future research in a larger sample and support the exploration, cross-ectionally and prospectively, of the relationship of clinician resiliency and changes in clinician resiliency with SE® training and clinical outcomes. These data have implications for other professions at risk of exposure to vicarious trauma including nurses, medical providers and paramedics.